(The Production of Chicken and Fish Feeds Using Some Substitution Materials) - Alamsyah, Rizal; F. Hutajulu, Turlan; Noerdin N.K, Mochamad; Junaidi, Lukman (Warta Industri Hasil Pertanian, 2000)
The study was aiming at investigating for both chicken and fish feet by using substitution materials which so far is used as by product. These substitution feeds were comprised of palm oil sludge, shrimp shell, gold snail, and by product from leather fleshing. Feed formulation, were based and Least square methods represented in Feedmania program and calculated by using computer. These raw materials can be substituted for amount parts of conventional materials e.g. yellow corn, soybean meal, and fish meal. Based on feed consumed for broiler chicken, it is obtained the result as follow feed convertion ratio (FCR) was 1.95/1, and the feed efficiency for fish was 41%.